SALT TOLERANCE IN UPLAND COTTON GENOTYPES TO NaCl SALINITY AT EARLY GROWTH STAGES - Z. Bibi; N. U. Khan; A. Latif; M. J. Khan; G. Manyuan; Y. Niu; Q. U. Khan; M. J. Khan; I. U. Khan; S. Shaheen; G. U. Sadozai (Journal of Animal and Plant Sciences, 2016)
Eight upland cotton genotypes (CIM-446, CIM-473, CIM-496, CIM-499, CIM-506, CIM-554, CIM-707 and SLH-284) were screened for salt tolerance with five NaCl salinity concentrations [0 mM (control), 50, 100, 150 and 200 mM] at early growth stages. Highly significant differences were observed among genotypes, salinity concentrations, and genotype vs. salinity interactions for growth variables. In the control (0 mM NaCl), genotypes showed enhanced vigor, however, response of genotypes at 50 mM NaCl was similar to the control, and for some traits, the response was increased as a result of stimulation by low salinity. Growth variable response gradually decreased as salinity concentrations increased (50 > 100 > 150 > 200 mM), while significant decrease were observed at 200 mM NaCl due high Na+ ion toxicity. The uptake of K+ and Na+ were inversely proportional, and Na+ accumulation was least in control and gradually increased as salinity application increased. Absorption of K+ was highest in the control and gradually decreased through increased salinity in shoot and root tissues. Genotype CIM-707 was most tolerant to salinity and exhibited the best performance for majority variables, followed by CIM-446. Identification of salt tolerant cotton genotypes for salt affected areas can benefit the farming community through increased crop yield.
Keywords: Cotton shoot and root tissues; growth variables; NaCl salinity concentrations; Na+ / K+ accumulation; salt tolerance; Gossypium hirsutum L.